2020
DOI: 10.1002/ajmg.a.61784
|View full text |Cite
|
Sign up to set email alerts
|

A case of rare isolated agnathia and literature review

Abstract: Agnathia is a rare congenital malformation with unknown etiology characterized by absence of the mandible, microstomia, and tongue aplasia, often found to have other anomalies including holoprosencephaly. The purpose of this paper was to describe the symptoms and imaging of a case of isolated agnathia and to conduct a comprehensive literature review of reported patients with isolated agnathia. Case reports of isolated agnathia are very rare, with most infants as stillborn. We report a child's management of iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(65 reference statements)
0
3
0
Order By: Relevance
“…Other diagnostic methods, such as CT and MRI, have also been employed to provide further details of the malformation. The differential diagnosis of the syndrome encompasses Treacher-Collins syndrome, Goldenhar syndrome, Nager syndrome, and Pierre Robin syndrome [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other diagnostic methods, such as CT and MRI, have also been employed to provide further details of the malformation. The differential diagnosis of the syndrome encompasses Treacher-Collins syndrome, Goldenhar syndrome, Nager syndrome, and Pierre Robin syndrome [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Alexander et al showed that 9 patients with isolated agnathia survived from 10 months to 27 years. In almost all cases, a tracheostomy was required to manage the acute airway obstruction [1]. Furthermore, Golinko et al reported 4 cases detailing various reconstructive strategies beyond infancy, as well as longitudinal follow-up into adulthood.…”
Section: Requirement Of the Exit Procedures In This Casementioning
confidence: 99%
See 1 more Smart Citation